2017
DOI: 10.1007/s11538-017-0321-2
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative to Moment Closure

Abstract: Moment closure methods are widely used to analyze mathematical models. They are specifically geared toward derivation of approximations of moments of stochastic models, and of similar quantities in other models. The methods possess several weaknesses: Conditions for validity of the approximations are not known, magnitudes of approximation errors are not easily evaluated, spurious solutions can be generated that require large efforts to eliminate, and expressions for the approximations are in many cases too com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In such cases it is sometimes possible to derive a set of ODEs, sufficient in number to define a completely specified system of estimated parameters. For a discussion of evolution of moment ODEs and associated closure techniques refer to, for example, Kuehn (2016) and Nasell (2017). Despite the system being closed and thus admitting recursive solutions, mathematically it can be demonstrated that equations describing the evolution of higher moments (n ≥ 2) are all defined by a composite expression of the same parameter set {Θ ̂1, Θ ̂2, Θ ̂3} and thus the under specification-problem is not removed.…”
Section: Approximation Methods Threementioning
confidence: 99%
“…In such cases it is sometimes possible to derive a set of ODEs, sufficient in number to define a completely specified system of estimated parameters. For a discussion of evolution of moment ODEs and associated closure techniques refer to, for example, Kuehn (2016) and Nasell (2017). Despite the system being closed and thus admitting recursive solutions, mathematically it can be demonstrated that equations describing the evolution of higher moments (n ≥ 2) are all defined by a composite expression of the same parameter set {Θ ̂1, Θ ̂2, Θ ̂3} and thus the under specification-problem is not removed.…”
Section: Approximation Methods Threementioning
confidence: 99%